Concept of collapsibility/new interior design approach: a design framework for understanding and designing change and impermanence - Said, Lore (The University of Edinburgh, 2020)
In this thesis, I argue that in a world characterised by change, contemporary interior designers lack competent guidance on how to interpret and design notions of impermanence, and how to experiment through practice with ways of doing so. The thesis presents a considered investigation into how the concept of 'collapsibility' might contribute to interior design processes while challenging what it describes as the 'current principles of permanence and stability'. Its central argument is: collapsibility should not be understood merely as a mechanistic or functional response to modern life, but rather as a folding, and unfolding and then refolding event, constantly changing and merging in fields of forces. Collapsibility is a commonly used concept for designing objects with predefined functions such as space saving, as described in Collapsibles: A Design Album of Space-Saving Objects by designer Per Mollerup (2001). This research extends beyond such teleological approaches to the concept of collapsibility as a mere mechanism, to suggest that the concept of collapsibility can be understood in a wider prospect as a design approach for both understanding and designing notions of change and impermanence in the 21st century. While my primary definition of the concept of collapsibility in this thesis is informed by designer Per Mollerup’s approach in his album ‘Collapsibles’, my extended approach of the concept of collapsibility in relation to impermanence and change is informed by a wider conceptual framework that is constructed through use of literature: The Fold by Deleuze, Form-Finding by Frei Otto and Soft Logic by Michel Serres. This conceptual framework developed in tandem with my hands-on approach of observing and making collapsible events using semiotic analysis and design practices as prime methods. I analyse collapsible events that happen throughout an everyday life and collapsible events of Bedouin tents. I then make collapsible structures to experiment with how collapsible events operate in a tangible way. These various explorations resulted in a new framework of the concept of collapsibility, in which I explore its practical application in guiding a design process, of collapsible floor prototype, that challenges common design approaches of permanence and stability. Finally, I discuss practical and theoretical remarks of the thesis and conclude that the concept of collapsibility should be seen as a new way of thinking that assists designers in interpreting and designing notions of change and impermanence as they continue to emerge within interior design and architectural fields.
Keywords: interiors; change; collapsible; semiotic; permanence; impermanence; folds; force; event; floor